BS EN 50377-4-3. Connector sets and interconnect components to be used in optical fibre communication systems. Product specifications. Part 4-3. Type SC/APC simplex 9° terminated on EN 60793 2 50 of type B-652.D and B-657.A singlemode fibre with full zirconia ferrule, category OP (26th March 2020) - British Standards Institution,
No abstract available